Determination of Daidzein and Genistein Contents in Mangifera Fruit. - Khoo, Hock Eng; Ahmad, Ismail (Nutrition Society of Malaysia, 2008)
The aim of this study was to determine the daidzein and genistein contents in Mangifera fruits. Three Mangifera species namely ‘bacang’ (Mangifera foetida), ‘kuini’ (M. odorata) and ‘bambangan’ (M. pajang) each from two different locations were selected. The extraction of isoflavones was carried out at 80oC for 30, 60 and 90 min. HPLC method was performed with a flow rate of 1.00 ml/min using three different separation columns to determine isoflavone contents. The Zorbax Eclipse RP C18 reverse-phase column was found to give the best resolution for isoflavone separation in Mangifera fruits. Moreover, extraction time of 90 min was found to increase the isoflavone aglycone contents. At optimised condition, ‘kuini’ had relatively high daidzein (9.4-10.5 mg/100 g) and genistein (1.6-1.7 mg/100 g) contents. Daidzein content of ‘bambangan’ (8.3-8.7 mg/100 g) was higher than ‘bacang’, but the genistein content of ‘bambangan’ (0.4-0.6 mg/100 g) was similar to that of ‘bacang’ (0.4-0.8 mg/100 g). However, there was a variation in daidzein and genistein contents in Mangifera fruits between two geographical locations.